Use of a demonstration project to evaluate viral survival in feed: Proof of concept. Issue 2 (26th June 2020) - Dee, Scott; Shah, Apoorva; Cochrane, Roger; Clement, Travis; Singrey, Aaron; Edler, Roy; Spronk, Gordon; Niederwerder, Megan; Nelson, Eric
Abstract: In 2014, the hypothesis that feed ingredients could serve as vehicles for the transport and transmission of viral pathogens was proposed and evaluated by multiple investigators under laboratory conditions. In an attempt to validate these data, we used a demonstration project to test whether three significant viruses of swine could survive in feed ingredients under real‐world shipping conditions. Samples of soya bean meal (organic and conventional), lysine, choline and vitamin A were spiked with a mixture of PRRSV 174, PEDV and SVA and transported for 21 days in the trailer of a commercial transport vehicle, encompassing 14 states and 9, 741 km. Samples were tested for viral genome and viability at the end of the transit period. Regarding viability, PRRSV, PEDV and SVA were all detected as infectious in bioassays following inoculation with both soy products. In addition, viable PRRSV and SVA were detected by bioassay pigs inoculated with samples of vitamin A, and infectious SVA was detected in pigs inoculated with samples of lysine and choline. These results provide further evidence that select viral pathogens of pigs can survive in certain feed ingredients during commercial transit.